Non‐canonical aging model systems and why we need them. (20th March 2017) - Valenzano, Dario Riccardo; Aboobaker, Aziz; Seluanov, Andrei; Gorbunova, Vera
Abstract : Aging is one of the greatest challenges for biomedical research in the developed world. The continuing increase in lifespan without accompanying increases in health span has extreme economic and societal implications for an aging society. The majority of adult‐onset diseases such as cancer, cardiovascular disease, and Alzheimer's are a direct consequence of aging, and with changing demographics, more and more people are afflicted. If we knew how to slow down the negative effects of aging, we could delay or prevent all of these diseases at once. We therefore need to understand the underlying molecular mechanisms of aging and longevity so as to develop applications that ultimately improve health span. Abstract : Aging research has yielded valuable knowledge into the molecular mechanisms of aging and longevity. Expanding the existing model organisms with extremely long‐ or short‐lived species, such as the African turquoise killifish, the planarian flatworm or the naked mole rat, could yield new insights into their unique adaptations and provide platforms on which to test interventions against aging processes.